An Enhanced IPv6 Anycast Routing Protocol Using Protocol Independent Multicast-Sparse Mode With Mobile IPv6 - Sulaiman, Aus M. (2007)
Anycast routing is an efficient routing mechanism that enables the network to choose the nearest and most appropriate server very quickly. However, IPv6 Anycast is not used widely in practice yet, and there are many reasons for this. Firstly, IPv6 Anycast does not have its own standard protocol because anycast builds its anycast membership tree like multicast does but unlike multicast it sends only to one of the groups using unicast mechanism. The other problem is that IPv6 Anycast mechanism could not provide stateful connections between the sender and the receiver because the sender always change the receiver based on the metric or the distance. In this thesis a new IPv6 anycast routing protocol is developed to provide a stateful communication between the anycast sender and the receiver. Protocol Independent Multicast-Sparse Mode (PIM-SM) has been chosen to establish the new IPv6 anycast mechanism because of many similar properties between multicast and anycast. A new variable is proposed in the routing table called Best Metric Factor (BMF) to describe the status of the receiver (free or Busy). This factor is used to decide the appropriate receiver to choose, the advantage of the proposed design can be observed easily when there are multi-anycast senders sending their traffic to the appropriate receiver at the same time. Next we improve the mechanism by building a direct connection between the anycast sender and the anycast receiver using route optimization by mapping the objects in Mobile IPv6 to the objects in the proposed mechanism. This is because there are many similar properties between Mobile IPv6 and the proposed design. The proposed mechanism has been shown to achieve a good performance with multi-anycast senders and can provide a stateful communication between the sender and the appropriate receiver.